PENGARUH PENGGUNAAN MOBILE BANKING (M-BANKING) TERHADAP TINGKAT KEPUASAN NASABAH PADA GENERASI MILENIAL YANG MENJADI NASABAH DI BANK SYARIAH STUDI PADA MAHASISWA FAKULTAS FEBI UIN RADEN INTAN LAMPUNG - Melati, Jean Vania Dwi; Fasa, Muhammad Iqbal (STAI Darul Qalam Tangerang, 2025)
This study aims to determine whether perceived benefits, perceived security, perceived ease of use, and perceived trust influence customer satisfaction levels in using mobile banking among millennial customers of Islamic banks. This research uses a qualitative approach, with data collected through questionnaires distributed to students of the Faculty of Economics and Business Islam (FEBI) at UIN Raden Intan Lampung. The results show that perceived ease of use and perceived trust have a positive and significant effect on customer satisfaction. Meanwhile, perceived benefits and perceived security do not significantly affect customer satisfaction among students using mobile banking at FEBI. The study’s findings indicate that the use of mobile banking positively and significantly influences students’ interest in saving with Bank Syariah Indonesia (BSI) and has a moderate relationship, meaning it is neither too strong nor too weak but significant between satisfaction with mobile banking usage at BSI. This provides practical implications for Islamic banks to continuously improve the quality of mobile banking services to enhance customer satisfaction, especially among young people